The use of selenium for controlling plant fungal diseases and insect pests - Li, Qianru; Xian, Limei; Yuan, Linxi; Lin, Zhiqing; Chen, Xiaoren; Wang, Jianjun; Li, Tao (Frontiers in Plant Science, 2023)
The selenium (Se) applications in biomedicine, agriculture, and environmental health have become great research interest in recent decades. As an essential nutrient for humans and animals, beneficial effects of Se on human health have been well documented. Although Se is not an essential element for plants, it does play important roles in improving plants’ resistances to a broad of biotic and abiotic stresses. This review is focused on recent findings from studies on effects and mechanisms of Se on plant fungal diseases and insect pests. Se affects the plant resistance to fungal diseases by preventing the invasion of fungal pathogen through positively affecting plant defense to pathogens; and through negative effects on pathogen by destroying the cell membrane and cellular extensions of pathogen inside plant tissues after invasion; and changing the soil microbial community to safeguard plant cells against invading fungi. Plants, grown under Se enriched soils or treated with Se through foliar and soil applications, can metabolize Se into dimethyl selenide or dimethyl diselenide, which acts as an insect repellent compound to deter foraging and landing pests, thus providing plant mediated resistance to insect pests; moreover, Se can also lead to poisoning to some pests if toxic amounts of Se are fed, resulting in steady pest mortality, lower reproduction rate, negative effects on growth and development, thus shortening the life span of many insect pests. In present manuscript, reports are reviewed on Se-mediated plant resistance to fungal pathogens and insect pests. The future perspective of Se is also discussed on preventing the disease and pest control to protect plants from economic injuries and damages.